Novel Radiolabeled Bisphosphonates for PET Diagnosis and Endoradiotherapy of Bone Metastases - Pfannkuchen, Nina (Pharmaceuticals (Basel), 2017)
Bone metastases, often a consequence of breast, prostate, and lung carcinomas, are characterized by an increased bone turnover, which can be visualized by positron emission tomography (PET), as well as single-photon emission computed tomography (SPECT). Bisphosphonate complexes of (99m)Tc are predominantly used as SPECT tracers. In contrast to SPECT, PET offers a higher spatial resolution and, owing to the (68)Ge/(68)Ga generator, an analog to the established (99m)Tc generator exists. Complexation of Ga(III) requires the use of chelators. Therefore, DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), NOTA (1,4,7-triazacyclododecane-1,4,7-triacetic acid), and their derivatives, are often used. The combination of these macrocyclic chelators and bisphosphonates is currently studied worldwide. The use of DOTA offers the possibility of a therapeutic application by complexing the β-emitter (177)Lu. This overview describes the possibility of diagnosing bone metastases using [(68)Ga]Ga-BPAMD ((68)Ga-labeled (4-{[bis-(phosphonomethyl))carbamoyl]methyl}-7,10-bis(carboxymethyl)-1,4,7,10-tetraazacyclododec-1-yl)acetic acid) as well as the successful application of [(177)Lu]Lu-BPAMD for therapy and the development of new diagnostic and therapeutic tools based on this structure. Improvements concerning both the chelator and the bisphosphonate structure are illustrated providing new (68)Ga- and (177)Lu-labeled bisphosphonates offering improved pharmacological properties.